A study on factors influencing consumer loyalty towards smartphone brand / Nur Amalina Saad - Saad, Nur Amalina (Faculty of Business and Management, 2019)
In the competitive marketplace today, every smartphone brand are trying to enhance the own performance of product to satisfied their consumer and to attract the consumer to be loyal with the brand. The consumer will be loyal if they have a better experience with the product. Not even that, the product of smartphone brand have made accordingly to the consumer needs and wants towards the smartphone. Every brand of smartphone product main objectives is to attract the consumer to be loyal to the product from time to time. It is where the companies of smartphone brand want the consumer positioning the mind about their product of smartphone features that the companies of smartphone serve to the market. Usually the features and benefit must be differently from other the smartphone brand, so that the brand can be more outstanding from other brand.